2016
DOI: 10.1128/msphere.00273-16
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Screens Identify Parasite Genetic Factors Associated with Malarial Fever Response in Plasmodium falciparum piggyBac Mutants

Abstract: Though the P. falciparum genome sequence has been available for many years, ~40% of its genes do not have informative annotations, as they show no detectable homology to those of studied organisms. More still have not been evaluated via genetic methods. Scalable forward-genetic approaches that allow interrogation of gene function without any pre-existing knowledge are needed to hasten understanding of parasite biology, which will expedite the identification of drug targets and the development of future interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Although no consistent growth defect was observed upon deletion of any exported FIKK kinase after 120 hours under optimal cell culture conditions, a recent genetic screen indicated that disruption of some FIKKs may have a fitness defect over a longer time scale 69 , and some FIKKs were refractory to non-conditional gene deletion 70 . Additionally, FIKK9.3 has been implicated in providing some protection against elevated temperatures, suggesting it may be important during fever 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no consistent growth defect was observed upon deletion of any exported FIKK kinase after 120 hours under optimal cell culture conditions, a recent genetic screen indicated that disruption of some FIKKs may have a fitness defect over a longer time scale 69 , and some FIKKs were refractory to non-conditional gene deletion 70 . Additionally, FIKK9.3 has been implicated in providing some protection against elevated temperatures, suggesting it may be important during fever 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing PI(3)P levels by ectopically expressing a human PI3K, Vps34, in P. falciparum confers similar resistance ( Mbengue et al, 2015 ). Intriguingly, a phenotypic screen using piggyBac mutagenesis showed a reduced heat tolerance in a pfkelch13 -upregulated P. falciparum mutant ( Thomas et al, 2016 ). If Pfkelch13 expression is inversely correlated with PI(3)P levels, the phenotype observed with the pfkelch13 -upregulated strain presents an intriguing possibility that PI(3)P may be connected to parasite fitness under heat stress ( Mbengue et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This mutant carries a single transposon insertion in the 5’ UTR of k13 in the NF54 background. Studies utilizing QISeq verified the absence of other changes in the genomic background [ 23 , 24 ]. Given K13’s BTB and propeller domains structural similarity to the transcriptional regulator Keap1, we hypothesized that dysregulation of K13 will result in an altered transcriptome of functionally-connected genes.…”
Section: Introductionmentioning
confidence: 99%